2019
DOI: 10.1038/s41598-019-56305-1
|View full text |Cite|
|
Sign up to set email alerts
|

Differential immune response modulation in early Leishmania amazonensis infection of BALB/c and C57BL/6 macrophages based on transcriptome profiles

Abstract: The fate of Leishmania infection can be strongly influenced by the host genetic background. In this work, we describe gene expression modulation of the immune system based on dual global transcriptome profiles of bone marrow-derived macrophages (BMDMs) from BALB/c and C57BL/6 mice infected with Leishmania amazonensis. A total of 12,641 host transcripts were identified according to the alignment to the Mus musculus genome. Differentially expressed genes (DEGs) profiling revealed a differential modulation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 98 publications
(127 reference statements)
4
33
0
2
Order By: Relevance
“…However, the parasite can subvert the activation of macrophages to establish infection [36]. The genomic and transcriptomic networks during Leishmania infection have been providing interesting data regarding how Leishmania can to modulate the gene organization and gene expression of its host [37][38][39][40]. Additionally, we have observed differentially expressed genes profile during the different phases of parasite growth [37,38,41].…”
Section: Discussionmentioning
confidence: 82%
“…However, the parasite can subvert the activation of macrophages to establish infection [36]. The genomic and transcriptomic networks during Leishmania infection have been providing interesting data regarding how Leishmania can to modulate the gene organization and gene expression of its host [37][38][39][40]. Additionally, we have observed differentially expressed genes profile during the different phases of parasite growth [37,38,41].…”
Section: Discussionmentioning
confidence: 82%
“…Some of the miRNAs modulated during infection have been implicated in macrophage polarization, as shown for the M1 phenotype (miRNA-146 and miRNA-210) and for M2 phenotype (miRNA-130a, miRNA-130b, miRNA-155, miRNA-21, miRNA-19a, miRNA-23a, miRNA-125a, miRNA-125b, miRNA-26a, miRNA-26b, and miRNA-720) [73]. In this way, the transcription profile of murine macrophages indicates a mix of M1/M2 phenotypes in murine macrophages infected with L. amazonensis, whereas in BALB/c macrophages, differential downregulation of Il1b is observed once C57BL/6 macrophages upregulate Il1b, a molecule that mediates nitric oxide (NO) production and confers resistance against Leishmania infection [74,75].…”
Section: Leishmania-host Interactionsmentioning
confidence: 99%
“…The parasite is able to subvert the host response at multiple levels including modification of cytokines, chemokines, and their receptor expression, preventing antigen presentation by major histocompatibility complex (MHC) class II molecules and killing mechanisms through reduction of NO production. This impairment of immune response, early in infection, favors parasite establishment and development of chronic disease ( Ji et al, 2003 ; Aoki et al, 2019 ). Several studies showed that L. amazonensis induces TGF-β production early in infection.…”
Section: Discussionmentioning
confidence: 99%
“…infection. BALB/c and C57BL/6 non-infected macrophages present over 500 genes differentially expressed, which probably influences host response in the event of an infection ( Aoki et al, 2019 ). Similarly, Probst et al (2012) showed significant differences between C57BL/6 and CBA macrophages baseline gene expression profiles, suggesting that the higher capacity to control L. amazonensis infection by C57BL/6 macrophages is due to the baseline transcriptional signature of these cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation